2016
DOI: 10.1111/pce.12766
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐dependent aerenchyma formation in adventitious roots is regulated differently in rice and maize

Abstract: In roots of gramineous plants, lysigenous aerenchyma is created by the death and lysis of cortical cells. Rice (Oryza sativa) constitutively forms aerenchyma under aerobic conditions, and its formation is further induced under oxygen-deficient conditions. However, maize (Zea mays) develops aerenchyma only under oxygen-deficient conditions. Ethylene is involved in lysigenous aerenchyma formation. Here, we investigated how ethylene-dependent aerenchyma formation is differently regulated between rice and maize. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 62 publications
4
61
0
Order By: Relevance
“…This finding suggests that ethylene is involved not only in inducible aerenchyma formation but also in constitutive aerenchyma formation. This evidence was confirmed by Yamauchi et al (2016), who found that 1-MCP also partially suppressed aerenchyma formation in rice roots in aerated nutrient solution. The formation of some aerenchyma even when roots were treated with 1-MCP (Yukiyoshi and Karahara, 2014;Yamauchi et al, 2016) could indicate that constitutive aerenchyma formation in rice roots is regulated by an ethyleneindependent pathway, as well as the ethylenedependent pathway, if the 1-MCP treatment blocked all perception of ethylene.…”
Section: The Process Of Ethylene-dependent Lysigenous Aerenchyma Formsupporting
confidence: 57%
See 1 more Smart Citation
“…This finding suggests that ethylene is involved not only in inducible aerenchyma formation but also in constitutive aerenchyma formation. This evidence was confirmed by Yamauchi et al (2016), who found that 1-MCP also partially suppressed aerenchyma formation in rice roots in aerated nutrient solution. The formation of some aerenchyma even when roots were treated with 1-MCP (Yukiyoshi and Karahara, 2014;Yamauchi et al, 2016) could indicate that constitutive aerenchyma formation in rice roots is regulated by an ethyleneindependent pathway, as well as the ethylenedependent pathway, if the 1-MCP treatment blocked all perception of ethylene.…”
Section: The Process Of Ethylene-dependent Lysigenous Aerenchyma Formsupporting
confidence: 57%
“…However, a greater amount of aerenchyma also would facilitate some venting of this ethylene from the roots (Visser and Pierik, 2007); such venting would only impact aerenchyma formation if ethylene then remained below the threshold concentration required, but this seems unlikely. Exogenously supplied ACC increased ethylene production and aerenchyma formation in rice roots under aerobic conditions (Yamauchi et al, , 2016), demonstrating that a low level of ACC production is likely rate limiting for ethylene biosynthesis in these aerobic roots. On the other hand, the levels of ethylene production in roots of rice and maize reflected the levels of ACO expression; a higher ACO expression level in rice roots than in maize roots under aerated conditions was associated with a more pronounced increase of ethylene production in rice roots than in maize roots immediately after the onset of low-oxygen conditions (Yamauchi et al, 2016).…”
Section: The Process Of Ethylene-dependent Lysigenous Aerenchyma Formmentioning
confidence: 99%
“…), which may promote grass survival under hypoxia (Yamauchi et al . ), and were also found in other African grasses (Baruch ). Although these responses supported the broader distribution of these exotic species in comparison with U. decumbens , these two species were more affected by soil waterlogging than the two most widespread native grasses at our study sites ( L. chrysothrix and T. spicatus ).…”
Section: Discussionsupporting
confidence: 63%
“…In species such as rice, some root aerenchyma form in the absence of flooding and additional aerenchyma form in response to flooding or ethylene treatment (Yamauchi, Shimamura, Nakazono, & Mochizuki, 2013). In maize, accumulation of aerenchyma is induced by hypoxia (Drew et al, 2000;Yamauchi et al, 2016). In contrast, the wetland species Juncus effusus form root aerenchyma in the absence of ethylene and flooding (Visser & Bogemann, 2006).…”
Section: )mentioning
confidence: 99%